CopyCatchers are versatile active genetic elements that detect and quantify inter-homolog somatic gene conversion - Zhiqian Li (Nature Portfolio, 2021)
CRISPR-based genetic elements can copy themselves across host genomes. Here the authors introduce CopyCatcher, a gene-drive related system for detecting and quantifying somatic gene conversion events.